On the complexity of urban lifeline systems - Leong, Leonard Shi Yuan (2016)
The FYP paper aims to investigate and model cascading failures in complex infrastructural systems, such as practical power networks. The investigation involves a series of risk assessment processes which reveals the intricacies and interdependencies of infrastructural systems in question. The studies and researches conducted in order to present meaningful data contributions for future urban systems planning. Such urban lifeline systems may encompass that of water supply, power supply and transportation, all of which are extremely essential and pivotal for a fully-functioning modern society. The project is theoretical and numerical in nature, and the investigations are centered on electrical and power network systems. The study aims to reveal the effects of various triggering events on network systems in question understand the extent of influence on performance loss and power redistributions, whether these influences of increasing magnitudes lead to cascading failures and eventual system shut downs. Triggering events affecting these networks are natural hazards, namely earthquakes, which are random and non-targeted disruptions in nature. These nodal studies seek to reveal the more vulnerable links as well as the overall robustness of the network systems. Initial phases of the project involved a wide range of research conducted on the theory behind various models of cascading failures while the latter phases involved concrete coding and modelling practices to simulate these network system behaviors.